Optimization of Spot Welding for Peel load on SPCC Steel Sheets - Raden Edy Purwanto; Moh. Hartono; Yuniarto Agus Widodo (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2020)
Spot welding is a process of connecting two metal components through one or more connection points by using heat from electrical resistance which is carried by two electrodes to the metal to be connected with a certain welding time. The purpose of this study is to determine the effect of voltage and time of pressure used for spot welding on the shear strength and peel strength on the SPCC plate. The variables used in this study are independent variables of electric current variation of 2.30 V, 2.70 V, 3.20 V and time variation of 3 seconds, 4 seconds, and 5 seconds with 1mm plate thickness. The dependent variable in this study is the calculation of shear strength and peel strength in universal testing machine, and the controlled variable in this study is 1mm plate thickness characteristic of SPCC palate work piece. The research method was carried out using the ANOVA Factorial with the null hypothesis that there was no influence of the spot welding time and voltage on spot welding on the shear strength and strength of the SPCC material's peel. The results of the study are for the shear test seen from the calculation using MINITAB, the time variation of the pressure is no effect, while for the voltage and the combination of time suppression and voltage there is influence. For strength testing, the null hypothesis is rejected for all variations, which means that there is an influence on the strength of the peel test.